Perspectives of carbon paste electrodes in stripping potentiometry - Svancara, Ivan; Ogorevc, Bozidar; Hocevar, Samo B; Vytras, Karel (Analytical sciences, 2002)
The testing of various types of carbon paste electrodes (CPEs) for their use in stripping potentiometry was carried out by means of specially proposed procedures and by using various model analyte systems. CPEs containing three different pasting liquids (paraffin oil, silicone oil, tricresyl phosphate) were tested as supports for mercury- and gold films, and as substrates for electrolytic, adsorptive, ion-pair forming, and extractive accumulation. Test measurements in organic solvent-containing media and studies of some irreversible electrochemical reactions were performed as well. Individual examples to be studied allowed one to formulate and outline some perspectives of CPEs in potentiometric stripping analysis and related constant current stripping analysis.